Integrating ICT in English Language Teaching: Enhancing Students’ Engagement and Learning Outcomes in the Digital Era: Penelitian - Rimadhona, Marizka; Carmelya, Shelvi; Firdaus, Masagus (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The integration of Information and Communication Technology (ICT) into English Language Teaching (ELT) has transformed education into a more flexible and engaging learning environment. ICT enables both teachers and students to access information, interact, and collaborate more effectively. This study explores the ways ICT is applied in English classrooms, its impact on students’ engagement and learning outcomes, and the challenges teachers face in implementing ICT-based instruction. Using a qualitative descriptive approach, this research involved two English teachers and thirty vocational students from SMK YPIP Talang Ubi. Data were gathered through interviews, classroom observations, and questionnaires. The findings show that ICT helps increase students’ motivation, participation, and comprehension, especially through tools such as Google Classroom, YouTube, Quizizz, and Padlet. However, teachers still struggle with limited infrastructure, low digital literacy, and unstable internet access. The study concludes that ICT integration is essential in modern ELT but requires adequate training, institutional support, and technological readiness to be effective.